From Handlebar to Enucleation: Management and Prosthetic Outcome of a Severe Traumatic Globe Luxation - Harlin Farhani; Hendriati; Chaerena Amri; Delvi Saswita (HM Publisher, 2025)
Background: Traumatic globe luxation (TGL) is a rare, severe ocular emergency involving the complete displacement of the eyeball from the orbit. It presents a profound clinical challenge, demanding a rapid and accurate assessment of complex prognostic factors to guide the difficult decision between globe salvage and primary enucleation. Case presentation: A 33-year-old male presented 18 hours after a motorcycle handlebar strike to his left orbit. The examination revealed a left globe luxation with No Light Perception (NLP) vision, a total afferent pupillary defect, and complete ophthalmoplegia. Computed tomography confirmed a closed-globe injury with a superior orbital rim fracture and a large retrobulbar hematoma, but could not delineate soft tissue integrity. Surgical exploration revealed two critical, paradoxical findings: an anatomically intact optic nerve despite its functional death, and a catastrophic avulsion of five of the six extraocular muscles. The medial, lateral, and inferior recti, along with both oblique muscles, were detached, while the superior rectus muscle was uniquely spared. Conclusion: Based on the catastrophic loss of vascular supply from the avulsed muscles, which rendered the globe biologically non-viable, a primary enucleation was performed. This case suggests that in TGL, the integrity of the extraocular musculature is a paramount prognostic indicator, potentially superseding the anatomical status of the optic nerve in determining globe viability. It highlights the necessity of intraoperative exploration to definitively assess the extent of injury and illustrates a scenario where primary enucleation is not a treatment failure, but a definitive, rehabilitation-focused therapeutic strategy.